Синтез і фізико-хімічні властивості 3-(4-(трет-бутил)феніл)-5-(R-ілтіо)-4Н-1,2,4-тріазол-4-амінів - Аксьонова, Ілона Ігорівна; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Аксёнова, И. И.; Панасенко, А. И.; Кныш, Е. Г.; Aksyonova, I. I.; Panasenko, O. I.; Knysh, Ye. G. (Запорізький державний медичний університет, 2016)
Похідні 1,2,4-тріазолу отримали широке застосування в медичній практиці завдяки різноманітному спектру біологічної дії та низькій токсичності. Саме тому цей клас органічних сполук є особливо цікавим і перспективним для дослідження його фізико-хімічних, біологічних властивостей. З метою пошуку нових потенційно біологічно активних речовин синтезували 13 нових сполук, котрі не були описані раніше в науковій літературі, – 3-(4-(трет-бутил)феніл)-5-(R-ілтіо)-4H-1,2,4-тріазол-4-амінів, а також запропонували препаративні методи їхнього синтезу. Структуру нових речовин вивчили за допомогою сучасних інструментальних методів аналізу (хромато-мас-спектрометрія, ІЧ-, 1Н ЯМР-спектроскопія та елементний аналіз). Встановили: результати роботи підтверджують структуру цих сполук, що свідчить про можливість надалі їх застосовувати в біологічних дослідженнях. Производные 1,2,4-триазола получили большое применение в медицинской практике благодаря широкому спектру биологического действия и низкой токсичности, что, в свою очередь, обусловлено присутствием в их структуре триазольного цикла. Именно поэтому данный класс органических гетероциклических соединений является особенно интересным и перспективным для исследования его физико-химических и биологических свойств. С целью поиска новых потенциально биологически активных веществ было синтезировано 13 новых соединений, ранее не описанных в научной литературе, – 3-(4-(трет-бутил)-фенил)-5-(R-илтио)-4H-1,2,4-триазол-4-аминов, а также предложены препаративные методы их синтеза. Структура новых соединений была изучена с помощью современных инструментальных методов анализа (хромато-масс-спектрометрия, ИК, 1Н ЯМР-спектроскопия и элементный анализ). Установлено, что результаты исследований подтверждают структуру данных соединений. Это свидетельствует о возможности их дальнейшего применения в биологических исследованиях. Aim. 1,2,4-triazole derivatives are widely used in medical practice due to its wide range of biological effect and small toxicity. This fact makes this class of organic heterocyclic compounds especially interesting and promising for the study of their physical-chemical and biological properties. Thirteen novel compounds, namely 3-(4- (tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazole-4-amines, that were not previously described in the literature, have been synthesized with the aim of search for new potentially biologically active compounds. Methods and results. In order to create new biologically active compounds 13 novel 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazole-4-amines have been synthesized, preparative methods of their synthesis have been proposed, the structure of synthesized compounds has been confi rmed by IR-, 1H NMR-spectroscopy, chromatography-mass spectrometry and elemental analysis. In addition, the compounds have been tested for antimicrobial and antioxidative activities. Conclusions. A preparative methods of synthesis of 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazol-4-amines that can be used for chemical modeling of new biologically active compounds are described. The structure of the synthesized compounds was confi rmed by complex of modern methods of investigation, namely: IR-, 1H NMR-spectroscopy, chromatography-mass spectrometry and element analysis. This indicates the possibility of using these substances to further biological studies.
Синтез и физико-химические свойства 3-(4-(трет-бутил)фенил)-5-(R-илтио)-4H-1,2,4-триазол-4-аминов
Synthesis and physical-chemical properties of 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazol-4-amines
Keywords: органічний синтез; похідні; амінотріазол; 1,2,4-тріазоли; органический синтез; производные; аминотриазол; 1,2,4-триазолы; Organic Synthesis; Derivatives; Aminotriazole; 1,2,4-triazoles